Enoxaparin-associated spontaneous breast haematoma in elderly with chronic kidney disease: a case report - Siti Salwa Shokri; Mohd Firdaus Mohd Hayati; Aishath Azna Ali; Suraya Othman; Nor Faezan Abdul Rashid; Shahrun Niza Abdullah Suhaimi (Gazi University, 2017)
Thomboembolic events are relatively common among elderly with restricted mobility. These adversities include deep vein thrombosis and pulmonary embolism that require anticoagulants as the mainstay of treatment. The elderly are not only at higher risk of thromboembolism, but also have a higher haemorrhagic complication especially among chronic kidney disease. Physicians should be cautious of haematoma formation if they present with sudden onset of painful breast swelling. We describe a rare case of an elderly with underlying chronic kidney disease who developed spontaneous right breast haematoma after taking low molecular weight heparin for her recently diagnosed pulmonary embolism.